Dispersion-tunable low-loss implanted spin-wave waveguides for large magnonic networks - Bensmann, Jannis; Schmidt, Robert; Nikolaev, Kirill O.; Raskhodchikov, Dimitri; Choudhary, Shraddha; Bhardwaj, Richa; Taheriniya, Shabnam; Varri, Akhil; Niehues, Sven; El Kadri, Ahmad; Kern, Johannes; Pernice, Wolfram; et al. (Nature materials, 2025)
Magnonic networks based on magnetic insulators are poised to revolutionize information processing due to their energy efficiency. However, current experimental realizations of spin-wave waveguides, which constitute the building blocks of such a network, suffer from limited spin-wave propagation lengths and inefficient dispersion tuning capabilities. Here we realize low-loss spin-wave waveguides in yttrium iron garnet thin films using silicon ion implantation, which creates an amorphous waveguide cladding. We measure spin-wave decay lengths exceeding 100 µm in submicrometre waveguides. The dispersion of the waveguides can be continuously tuned due to the precise and localized ion implantation, which sets them apart from commonly etched waveguides. Using our maskless waveguide definition, we demonstrate a large-scale magnonic network consisting of 198 crossings, paving the way for wafer-scale magnonic integrated circuits.